Imej Islam: Tanggapan Negatif dan Penyelesaiannya - Ibrahim, Ismail (Jurnal Usuluddin, 1995)
The significance of this article lies in it description social life in Islam which should be truly understood by Muslims as well as non-Muslim. So, they can evaluate the virtues of the religion.